Antibody–drug conjugates in lymphoma. (October 2014) - Nathwani, Nitya; Chen, Robert
Antibody–drug conjugates (ADCs) are comprised of monoclonal antibodies physically linked to cytotoxic molecules. They expressly target cancer cells by delivering cytotoxic agents to cells displaying specific antigens, and minimize damage to normal tissue. The efficacy and tolerability of these agents are primarily determined by the target antigen, the cytotoxic agent and the linker connecting the cytotoxic agent to the monoclonal antibody. Following advances in technology, clinical trials have demonstrated greater efficacy for ADCs compared with the corresponding naked monoclonal antibodies. This review summarizes the features of current clinically active ADCs in lymphoma and emphasizes recent clinical data elucidating the benefit of antibody-directed delivery of cytotoxic agents to tumor cells.